Digital Technologies for Agricultural and Rural Development in the Global South 2018
DOI: 10.1079/9781786393364.0092
|View full text |Cite
|
Sign up to set email alerts
|

Towards alternate theories of change for M4ARD.

Abstract: This chapter explores alternative theories of change for mobile technologies for agriculture and rural development. It critically examines two theories of change (the 'market efficiency' and 'knowledge dissemination' theories) and highlights some of the challenges they have faced in practice. In response to these challenges, an alternative approach to developing a theory of change is suggested, which draws upon human development theories. A case study of an ongoing research project exemplifies such an alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Importantly, there is often a misalignment between the way farmers learn about farming and the way interventions based on contemporary technologies are delivered (Kendall & Dearden, ; Oreglia, ). As an example, Kendall and Dearden () found that IVR systems (which can be used by farmers to SMS questions) provided short‐term and succinct answers to farmers' questions (eg, around dealing with pests); however, often more holistic and long‐term responses were required to address underlying problems and to stimulate positive change in practices. This was not always possible by means of contemporary technologies.…”
Section: Agriculture and Ict In Rural Africamentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, there is often a misalignment between the way farmers learn about farming and the way interventions based on contemporary technologies are delivered (Kendall & Dearden, ; Oreglia, ). As an example, Kendall and Dearden () found that IVR systems (which can be used by farmers to SMS questions) provided short‐term and succinct answers to farmers' questions (eg, around dealing with pests); however, often more holistic and long‐term responses were required to address underlying problems and to stimulate positive change in practices. This was not always possible by means of contemporary technologies.…”
Section: Agriculture and Ict In Rural Africamentioning
confidence: 99%
“…Building on this, Hudson et al () study found that a combination of both radio and mobile channels for information dissemination greatly increased not only awareness but also adoption of new farming practices. This is suggestive of the need to move away from purely technical solutions and towards an emphasis on “valued ways of being and doing” (Kendall & Dearden, , p.13). In other words, development actors' effectiveness in stimulating agricultural development via contemporary technologies may well be dependent on developing strategies that accommodate normative rural practices, understanding synergies among various contemporary and legacy technologies, and capturing the complexity of the rural information environment (Hayes & Westrup, ; Kendall & Dearden, ).…”
Section: Agriculture and Ict In Rural Africamentioning
confidence: 99%
See 3 more Smart Citations